Stand density management diagram for Nothofagus glauca [Phil.] Krasser second growth forests in Chile - Muñoz, Fernando; Cancino, Jorge; Rodríguez, Roque (Instituto de Ecología, A.C., 2018)
The density management diagrams describe graphically the size-density relationship, which is a tool that facilitates the planning and monitoring of silvicultural interventions. Despite the importance of this information, no diagrams for N. glauca, an endemic tree of central Chile, which is considered as a representative species of the mediterranean forests of Nothofagus genus, are known. A total of 200 temporary plots were used to obtain the size-density model, established in the distribution area of the species. This model was then modified to obtain maximum density curves and build density management diagram. The obtained results suggest to its application reference curves of 55% (beginning of self-thinning) and 35% (load site capacity inferior limit).